Evaluating action plans - J. W. Grobbelaar; J. J. Murphy; S. R. Van Der Walt (South African Journal of Business Management, 1986)
In 1976 Louis Gerstner wrote, 'one of the most intriguing management phenomena of the late 1960's has been the rapid spread of the corporate planning concept. Except for the so-called computer revolution, few management techniques have swept through corporate and government enterprise more rapidly or completely'. Yet in spite of this explosion of companies doing corporate planning there are still areas within the process that need to be researched. One such area is the 'evaluation of the action plan'. How do managers decide which portfolio of action plans to select and implement? It has been the authors' experience that these decisions are mostly made on 'gut' feel with a great deal of politicking taking place. In this article a methodology is developed to assist managers in the comparative evaluation of action plans, the final decisions being based on the use of a multivariate model which relates achievement and risk.
Keywords: 650